Hubungan Tingkat Pengetahuan terhadap Perilaku Swamedikasi Common Cold di Apotek X Kabupaten Nganjuk - Nur Fahma Laili; Anggi Restyana; Neni Probosiwi; Lisa Savitri; Elly Megasari; Tridoso Sapto A; Evi Laela Sari; La’ally Maula (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Common cold or salesmas is an upper respiratory tranct infection caused by a virus. Therapy of the common cold can be done through self-medication. Self-medication is a form of community effort to maintain and increase health level. Self-medication requires good knowledge to result good behavior. This study aims to determine the corelation between knowledge on the behavior of self-medication of common cold in apotek x Nganjuk regency. This research is a descriptive observational study with a cross sectional research design with data collection through knowledge and behavior questionnaires. From the research results obtained 104 research respondents who met the inclusion criteria. The results obtained are high level of knowledge (59.6%), moderate (38.5%), low (1.9%), for the level of good behavior (73.1%), moderate (24.0%), less (2.9%). The significance value obtained is 0.000 and and the value of the correlation coefficient with a strong positive correlation direction of 0.513 which means that there is a relationship between the level of knowledge on the behavior of self-medication of common cold in apotek x in Nganjuk regency.